Keragaman Spora Cendawan Patogen dengan Spora Trap di Agroekosistem Rawa Kalimantan Tengah - Dini Yuliani; Santoso Santoso; Agus W Anggara (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
Initial information on spore populations of pathogenic fungi is needed to anticipate opportunities for rice disease to develop in swamps and to take early steps in disease control efforts. Disease control by suppressing the initial inoculum and its rate of development has a high chance of success and is preventive. The purpose of this study was to obtain information on the diversity of fungal spore populations in the air using spore traps in the swamp rice agroecosystem of Central Kalimantan. The research was carried out in the 2021 planting season at the swamp rice production center, namely Blanti Siam, Central Kalimantan. The study of the diversity of the fungal spore population was carried out in a display location of 14 ha of rice varieties and 66 ha of rice demfarm. For the display of rice varieties, 14 spore traps were installed, while at the demfarm location, 22 spore traps were installed. Observations of spore traps were carried out 4 times starting from nursery/tillage and continued for each stage of rice plant growth. Identification of fungal pathogens was carried out based on the morphological characteristics of the spores/conidia with the aid of a microscope. The results of the identification of the spore trap on the display of rice varieties and rice demfarm obtained spores of Rhizopus sp., Helminthosporium sp., Fusarium sp., Pyricularia oryzae, Alternaria sp., Cercosporella sp., and nematodes. Helminthosporium sp. found to be very dominant in both locations. Pyricularia oryzae was obtained in very low quantities. This is related to the low rate of blast disease at the location of rice display and rice demfarm. Fusarium sp., Alternaria sp., Cercosporella sp., and nematodes were found to be very low in spore traps.